2014
DOI: 10.1016/j.nicl.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity analysis of brain activation in fMRI

Abstract: In many brain diseases it can be qualitatively observed that spatial patterns in blood oxygenation level dependent (BOLD) activation maps appear more (diffusively) distributed than in healthy controls. However, measures that can quantitatively characterize this spatial distributiveness in individual subjects are lacking. In this study, we propose a number of spatial heterogeneity measures to characterize brain activation maps. The proposed methods focus on different aspects of heterogeneity, including the shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Amzica et al showed that disconnection of intracortical synaptic linkages in anesthetized cats disrupts synchronization of slow oscillations (Amzica and Steriade, 1995 ). Gupta et al showed that long range connectivity as measured by functional magnetic resonance imaging was changed after diseases and this altered spatial heterogeneity (Gupta et al, 2014 ). Ibrahim et al found that ipsilateral functional connectivity was increased after a functional hemispherotomy in which one hemisphere was disconnected from the other (Ibrahim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amzica et al showed that disconnection of intracortical synaptic linkages in anesthetized cats disrupts synchronization of slow oscillations (Amzica and Steriade, 1995 ). Gupta et al showed that long range connectivity as measured by functional magnetic resonance imaging was changed after diseases and this altered spatial heterogeneity (Gupta et al, 2014 ). Ibrahim et al found that ipsilateral functional connectivity was increased after a functional hemispherotomy in which one hemisphere was disconnected from the other (Ibrahim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while one surveys fMRI signals, a detail must not be ignored that these signals, like many other physiological time series, commonly exhibit extremely inhomogeneous and non-stationary fluctuations in an irregular and complex manner [ 4 , 5 ]. We hypothesize that these complexity/regularity could be modulated in pertinent cognitive tasks, and they may change through experimental paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Previously applied functional connectivity methods also showed significant differences between patients with Rolandic epilepsy and controls in these regions (Rolandic strip, language regions, and default mode network regions) in the literature . However, it needs to be remarked that a spatial overlap (SPM) analysis, as applied in this study, only reveals brain areas that coherently over the patients show abnormalities in the time series signal, while more heterogeneously (spatially) distributed abnormalities may remain undetected …”
Section: Discussionmentioning
confidence: 69%